Psychosocial and cognitive risk factors for orthorexia nervosa: an integrative review of recent literature - Vitória Morelli Guerrazzi; Isadora Paiva Abbondanza; Leticia Bragalia Passarella; Emily Godoi Pereira; Thiago Bonafé; Maíra Pieri Ribeiro (Debates em Psiquiatria)
Introduction: Orthorexia nervosa (ON) is a dysfunctional eating behavior characterized by an obsession with healthy eating. This disorder is influenced by psychological, social, and behavioral factors, with social media being a central factor. Digital content that promotes restrictive diets and fitness practices has contributed significantly to the dissemination of rigid and potentially harmful eating patterns, especially among adolescents and women. Objective: This review aimed to identify the main psychosocial and cognitive predisposing factors associated with ON, with an emphasis on the role of social media and other underlying mechanisms. Method: This is an integrative literature review, conducted according to the PRISMA guidelines. The review protocol was registered with PROSPERO CRD42024594857. Fourteen recently published studies were analyzed, totaling a sample of 12,628 participants. Inclusion criteria involved studies that addressed psychological, social, or behavioral risk factors related to ON. Results: Social media was strongly associated with ON, especially those that promote restrictive diets and fitness content. Dietary patterns such as vegan or gluten-free diets, combined with compulsive exercise, contribute to the maintenance of a pathological cycle. Psychological factors such as insecure attachment styles, low self-esteem, and difficulties in emotional regulation increase the risk. Mindfulness showed varied effects, while self-compassion stood out as a possible protective factor. Conclusion: Coping with ON requires a multifaceted approach, with clearer diagnostic criteria, public health actions to reduce the impact of social networks, and interventions focused on underlying psychological factors. Future research should prioritize early identification and prevention strategies.